On History and Memory - Třeštík, Dušan (Dějiny – teorie – kritika, 2023)
Against the background of the current debates in the Czech Republic on the "purity of history" and the need to protect some notional "correct history", practised by professionals, from the meddling and disinterpretation of journalists, politicians and the public in general, the author draws attention to the headway being made by contemporary research on the historial "memory" of nations and other groups. While obviously "Memory" is not "correct", it is authentic and legitimate. It is not the enemy of the history produced by professinals, but its partner in dialogue. Historians must conduct such a dialogue with a public on the broadest possible basis, must open themselves up to it and not hide from it behind dangerously cracked shield of their positivist scientism.